TINGKAT PENGETAHUAN SUAMI TENTANG TANDA BAHAYA NIFAS BERHUBUNGAN DENGAN DUKUNGAN MASA NIFAS - Winancy Winancy (Poltekkes Kemenkes Jakarta III, 2017)
Puerperal period is a time of risk of complications for the mother because the reproductive organs in the process of recovery. Families and postpartum women are not aware of it because the focus of their attention is on the newborn. Postpartum support is needed for a mother so that childbirth can be passed without complication. Support to mother's health and safety is done by the government through Safe Matherhood Program and Mother Love Movement (GSI). This study aims to determine the relationship between the level of knowledge and attitudes of husbands about the danger signs of puerperal with support during the postpartum period. Based on data from the Ministry of Health RI in 2012 showed thatpostpartum complications contribute as the cause of maternal mortality is quite high around 30.2%. This research is quantitative research with cross sectional design. The population consist of husbands of post pastum women with a sample of 97 respondents. the technique of sampling is done in a non random sampling in accordance with the criteria of inclusion and accidental sampling. The data using primary data in the form of a questionnaire. The results showed there was a significant relationship between knowledge and postpartum support. The husband's knowledge is a factor has an important influence on post partum support with p value < 0.05 (0, 005). Health education or counseling to the husband is important given how to increase the participation of the husband to providing support to his wife during puerperium.